Are risk aversion and impatience related to cognitive ability? - Thomas Dohmen; Armin Falk; David Huffman; Uwe Sunde (Institute for the Study of Labor (IZA), 2007)
Is the way that people make risky choices, or tradeoffs over time, related to cognitive ability? This paper investigates whether there is a link between cognitive ability, risk aversion, and impatience, using a representative sample of the population and incentive compatible measures. We conduct choice experiments measuring risk aversion, and impatience over an annual time horizon, for a randomly drawn sample of roughly 1,000 German adults. Subjects also take part in two different tests of cognitive ability, which correspond to sub-modules of one of the most widely used IQ tests. Interviews are conducted in subjects' own homes. We find that lower cognitive ability is associated with significantly more impatient behavior in the experiments, and with greater risk aversion. This relationship is robust to controlling for personal characteristics, educational attainment, income, and measures of credit constraints. We perform a series of additional robustness checks, which help rule out other possible confounds.
urn:nbn:de:101:1-20080402396
Keywords: 330; Verhalten; Risikopräferenz; Kognition; Bildungsniveau; Deutschland